2021
DOI: 10.3390/ijms22136749
|View full text |Cite
|
Sign up to set email alerts
|

External dsRNA Downregulates Anthocyanin Biosynthesis-Related Genes and Affects Anthocyanin Accumulation in Arabidopsis thaliana

Abstract: Exogenous application of double-stranded RNAs (dsRNAs) and small-interfering RNAs (siRNAs) to plant surfaces has emerged as a promising method for regulation of essential genes in plant pathogens and for plant disease protection. Yet, regulation of plant endogenous genes via external RNA treatments has not been sufficiently investigated. In this study, we targeted the genes of chalcone synthase (CHS), the key enzyme in the flavonoid/anthocyanin biosynthesis pathway, and two transcriptional factors, MYBL2 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…In our studies, the structural genes that regulated the phenylpropanoid biosynthesis pathways (43 genes), flavonoid biosynthesis pathways (22 genes), and anthocyanidin biosynthetic pathways (10 genes) were significantly expressed when the color of the leaves was changed (Figure 5). Among them, six PAL genes, nine 4CL genes, and six CHS genes were substantially expressed in red-colored leaves of A. triflorum, suggesting that these early biosynthetic genes lead to the production of flavonoids, as observed in other plant species with red leaves or fruits [39][40][41][42]. In addition, some downregulated PAL, 4CL, and CHS genes were also found in red leaves, suggesting that the color change in A. triflorum leaves was controlled by multiple single genes.…”
Section: Key Genes Related To Anthocyanin Synthesis In a Triflorum Le...mentioning
confidence: 77%
“…In our studies, the structural genes that regulated the phenylpropanoid biosynthesis pathways (43 genes), flavonoid biosynthesis pathways (22 genes), and anthocyanidin biosynthetic pathways (10 genes) were significantly expressed when the color of the leaves was changed (Figure 5). Among them, six PAL genes, nine 4CL genes, and six CHS genes were substantially expressed in red-colored leaves of A. triflorum, suggesting that these early biosynthetic genes lead to the production of flavonoids, as observed in other plant species with red leaves or fruits [39][40][41][42]. In addition, some downregulated PAL, 4CL, and CHS genes were also found in red leaves, suggesting that the color change in A. triflorum leaves was controlled by multiple single genes.…”
Section: Key Genes Related To Anthocyanin Synthesis In a Triflorum Le...mentioning
confidence: 77%
“…Several studies show that it is possible to down-regulate plant transgenes, including GFP , GUS , and YFP [ 24 , 25 , 26 , 27 , 28 ] or plant endogenous genes, including R2R3-MYB transcription factors, sugar transporter gene, a downy mildew susceptibility gene, and a chalcone synthase gene [ 19 , 20 , 21 , 22 , 23 ]. However, the number of reports on the effect of exogenous RNAs on the expression of specific plant gene targets is small and there are scarce data on the specificity and effectiveness of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is based on the exogenously induced RNAi (exoRNAi), which is induced by the application of the synthetic exogenous RNAs to the plant surfaces and is being developed as a promising alternative to transgenic plants and VIGS for plant pathogen protection. At the same time, there are few reports on the successful application of this strategy to downregulate expression of plant endogenous genes [ 19 , 20 , 21 , 22 , 23 ] or plant transgenes [ 24 , 25 , 26 , 27 , 28 ]. Several studies have reported downregulation of transgenes encoding green fluorescent protein (GFP), β-glucuronidase (GUS), yellow fluorescent protein (YFP), or neomycin phosphotransferase II ( NPTII ) during external application of dsRNA, siRNA, or hpRNA solutions of the leaf surface of tobacco or Arabidopsis [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanin and stilbene content analysis was performed by the method HPLC-MS as described [ 45 , 47 , 48 ]. Briefly, for anthocyanins 100 mg fresh cells tissue were subsequently homogenized using a mortar and a pestle in 1 mL of 1% ( v/v ) hydrochloric acid in methanol.…”
Section: Methodsmentioning
confidence: 99%